2016
DOI: 10.1074/jbc.m116.740050
|View full text |Cite|
|
Sign up to set email alerts
|

Glycosylation Alters Dimerization Properties of a Cell-surface Signaling Protein, Carcinoembryonic Antigen-related Cell Adhesion Molecule 1 (CEACAM1)

Abstract: Human carcinoembryonic antigen-related cell adhesion molecule 1 (C?/Au: EACAM1) is a cell-surface signaling molecule involved in cell adhesion, proliferation, and immune response. It is also implicated in cancer angiogenesis, progression, and metastasis. This diverse set of effects likely arises as a result of the numerous homophilic and heterophilic interactions that CEACAM1 can have with itself and other molecules. Its N-terminal Ig variable (Ig V ) domain has been suggested to be a principal player in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…Our recent high resolution crystal structure (2.04 Å) of the unglycosylated hCEACAM1 IgV domain (PDB ID 4QXW) [15,27] confirmed this by featuring two IgV molecules in the crystallographic asymmetric unit anchored at their respective GFCC'C" surfaces and confirmed at atomic level resolution the participation of critical CC' and FG loop residues determined previously to be necessary for hCEACAM1 homodimerization [30][31][32]. Nuclear magnetic resonance studies (NMR) on unglycosylated hCEACAM1 IgV additionally demonstrated the presence of an exclusive GFCC'C"-mediated IgV dimer in solution [31] thus further reinforcing the significance of the GFCC'C" face in mediating hCEACAM1 IgV homo-oligomerization.…”
Section: Ceacam1 Igv Domain Mediates Cis and Trans Oligomerization-supporting
confidence: 80%
See 1 more Smart Citation
“…Our recent high resolution crystal structure (2.04 Å) of the unglycosylated hCEACAM1 IgV domain (PDB ID 4QXW) [15,27] confirmed this by featuring two IgV molecules in the crystallographic asymmetric unit anchored at their respective GFCC'C" surfaces and confirmed at atomic level resolution the participation of critical CC' and FG loop residues determined previously to be necessary for hCEACAM1 homodimerization [30][31][32]. Nuclear magnetic resonance studies (NMR) on unglycosylated hCEACAM1 IgV additionally demonstrated the presence of an exclusive GFCC'C"-mediated IgV dimer in solution [31] thus further reinforcing the significance of the GFCC'C" face in mediating hCEACAM1 IgV homo-oligomerization.…”
Section: Ceacam1 Igv Domain Mediates Cis and Trans Oligomerization-supporting
confidence: 80%
“…Independent mutagenesis analysis of hCEACAM1 corroborated these latter results by showing the critical role of the GFCC'C" interface in determining the high affinity homodimerization of the hCEACAM1 IgV domain (Kd ~ 450 nM) [29], and specifically highlighting the contribution of the CC' (residues Y34, V39, D40, R43, Q44) and FG (residues Q89, I91) loops [30][31][32]. Our recent high resolution crystal structure (2.04 Å) of the unglycosylated hCEACAM1 IgV domain (PDB ID 4QXW) [15,27] confirmed this by featuring two IgV molecules in the crystallographic asymmetric unit anchored at their respective GFCC'C" surfaces and confirmed at atomic level resolution the participation of critical CC' and FG loop residues determined previously to be necessary for hCEACAM1 homodimerization [30][31][32]. Nuclear magnetic resonance studies (NMR) on unglycosylated hCEACAM1 IgV additionally demonstrated the presence of an exclusive GFCC'C"-mediated IgV dimer in solution [31] thus further reinforcing the significance of the GFCC'C" face in mediating hCEACAM1 IgV homo-oligomerization.…”
Section: Ceacam1 Igv Domain Mediates Cis and Trans Oligomerization-mentioning
confidence: 60%
“…These advances have been driven by the very low sample amounts obtainable from clinical sources, the extremely heterogeneous nature of glycan occupancies and structures, the need for high-throughput reliable analysis methods, and recent discoveries of more unusual glycoconjugates. 1316 …”
mentioning
confidence: 99%
“…Likewise, the ligand binding affinity of notch receptor increases when GlcNAc is added to fucose at a specific Thr, and it is affected by O‐fucosylation at conserved sites . Also, dimer formation of carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1), and thus, probably, its interaction with other molecules, is altered by glycosylation . Even the addition of a single GlcNAc at each of the three native N‐glycosylation sites in the Ig variable domain of CEACAM1 inhibited its dimerization in in vitro studies.…”
Section: Effects On Ligand Binding and Biological Functionsmentioning
confidence: 99%